2015
DOI: 10.1038/sc.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

Can combined aerobic and muscle strength training improve aerobic fitness, muscle strength, function and quality of life in people with spinal cord injury? A systematic review

Abstract: Study design: A systematic review. Objectives: The aim of this systematic review was to establish whether combined aerobic training and muscle strength training is effective in improving aerobic fitness, muscle strength, function and/or quality of life (QoL) in people with spinal cord injury (SCI). Settings: Faculty of Health Sciences. University of Sydney, NSW, Australia. Methods: A search was conducted for randomized controlled trials (RCTs), controlled trials, uncontrolled clinical trials, case series and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
1
26
0
2
Order By: Relevance
“…Studies have shown that participation in exercise activities has correlated with positive changes in physical functioning and QoL in individuals with SCI. [14][15][16][17] Bochkezanian completed a systematic review on exercise interventions in individuals with SCI and revealed that much of the literature is of low quality, however, a few studies on muscle strengthening and QoL demonstrated positive results. 14 Although the literature remains limited, de Oliveira et al demonstrated improvements in functional goals, self-esteem and QoL following an 8 to 12 week exercise program performed twice weekly.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that participation in exercise activities has correlated with positive changes in physical functioning and QoL in individuals with SCI. [14][15][16][17] Bochkezanian completed a systematic review on exercise interventions in individuals with SCI and revealed that much of the literature is of low quality, however, a few studies on muscle strengthening and QoL demonstrated positive results. 14 Although the literature remains limited, de Oliveira et al demonstrated improvements in functional goals, self-esteem and QoL following an 8 to 12 week exercise program performed twice weekly.…”
Section: Introductionmentioning
confidence: 99%
“…However, SCI-specific guidelines are based mainly on studies involving people with paraplegia ( van der Scheer et al, 2017 ). Tetraplegia-specific research is needed because although tetraplegia typically comprises between 40 and 60 percent of the population with traumatic SCI ( Noonan et al, 2012 ; Lee et al, 2014 ; Singh et al, 2014 ), systematic reviews of exercise intervention research indicate there is insufficient tetraplegia-specific data to make exercise prescriptions based on injury level ( Bochkezanian et al, 2015 ; van der Scheer et al, 2017 ). Given the additional functional limitations and impaired sympathetic nervous system function during exercise in tetraplegia ( Haisma et al, 2006 ; Cowley, 2018 ), it raises the question of whether 150 min weekly of exercise at moderate to high intensity would provide a similar benefit for those with tetraplegia compared to lower level SCI (paraplegia).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the loss of central activation and disuse results in muscle atrophy and further weakness [4]. There are many different interventions aimed at increasing voluntary strength in weak muscles following SCI, but surprisingly little evidence about their effectiveness [5][6][7][8][9][10]. The only exception to this is progressive resistance training [5,7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%